Lifetime body mass index and grip strength at age 46 years: the 1970 British Cohort Study. Issue 4 (19th May 2022) - Cooper, Rachel; Tomlinson, David; Hamer, Mark; Pinto Pereira, Snehal M.
Abstract: Background: Ongoing rises in obesity prevalence have prompted growing concerns about potential increases in the burden of age‐related musculoskeletal conditions including sarcopenia and sarcopenic obesity. This is of particular concern for future generations of older adults who have lived more of their lives in an obesogenic environment than current generations of older adults. We aimed to study longitudinal associations between body mass index (BMI) and grip strength in midlife using data from a large population‐based sample, the 1970 British Cohort Study (BCS70). Methods: BCS70 participants with valid measures of maximum grip strength at age 46 years were included in analyses [3671 males (49%) and 3876 females (51%)]. Using sex‐specific linear regression models, we examined associations of (i) BMI at ages 10, 16, 30, and 46 years; (ii) body fat percentage (BF%) and waist–hip ratio at age 46 years; (iii) BMI gains between 10–16, 16–30, and 30–46; and (iv) age at onset of obesity, with grip strength. Results: At age 46 years, mean (standard deviation) grip strength was 48.10 kg (8.98) in males and 29.61 kg (5.81) in females. Higher BMI at all ages was associated with stronger grip, and the scale of associations was greater in males than females from age 16 onwards ( P sex interactions < 0.01). For example, in fully adjusted models, a 1 standard deviation increase in BMI at age 16 was associated with mean differences in grip strength at age 46 years of 1.41 kg (95% confidence interval: 1.07, 1.75) in males and 0.72 kg (0.53, 0.91) in females. Higher BF% at age 46 was also associated with stronger grip in both sexes. Greater gains in BMI between ages 10 and 16 were associated with stronger grip in both sexes, but subsequent gains in BMI were only associated with stronger grip in males. Associations of greater length of exposure to obesity and stronger grip were also more consistent among males than females. For example, in fully adjusted models, mean grip strength at age 46 years of males and females who had been obese since age 10 or 16 years was 4.39 kg (1.85, 6.93) and 1.25 kg (−0.18, 2.69) higher than males and females who had never been obese, respectively. Conclusions: Higher BMI from childhood onwards is associated with stronger grip at age 46 years. This suggests that, at this age, anabolic effects of fat on muscle are outweighing the catabolic effects thought to lead to the manifestation of sarcopenic obesity later in life, especially among men. Midlife may be an optimal time to intervene to prevent sarcopenic obesity.